High treatment failure rate is better explained by resistance gene detection than by minimum inhibitory concentration in patients with urogenital Chlamydia trachomatis infection. (July 2020) - Shao, Lili; You, Cong; Cao, Junya; Jiang, Yong; Liu, Yuanjun; Liu, Quanzhong
Highlights: Minimum inhibitory concentrations (MICs) of macrolides and tetracyclines against Chlamydia trachomatis were comparable in the treatment success and treatment failure groups. The occurrence of gene mutations in 23S rRNA and tet (M) acquisition are better associated with clinical treatment outcomes of C. trachomatis infection than MICs. The A2057G, C2452A, and T2611C gene mutations of 23S rRNA were detected in C. trachomatis clinical isolates with azithromycin treatment. The detection of resistance genes may be a preferable assay for the prediction of treatment results compared with in vitro drug susceptibility tests. Abstract: Objective: The aim of this study was to investigate the relationships between treatment outcomes of patients with urogenital Chlamydia trachomatis infections and minimum inhibitory concentrations (MICs) and drug resistance genes. Methods: The clinical data of 92 patients diagnosed with Chlamydia trachomatis ( C. trachomatis ) infections were collected. Of these patients, 28 received regular treatment with azithromycin and 64 received minocycline. All patients underwent three monthly follow-ups after the completion of treatment. The microdilution method was used for the in vitro susceptibility tests. The acquisition of 23S rRNA mutations and presence of the tet (M) gene were detected by gene amplification and sequencing. Results: The MICs of azithromycin, clarithromycin, erythromycin, tetracycline, doxycycline, and minocycline were comparable for isolates from the treatment failure and treatment success groups. Higher detection rates of 23S rRNA gene mutations and tet (M) were found in the treatment failure group (57.14% and 71.43%, respectively) than in the treatment success group (14.29% and 30.23%, respectively) ( p < 0.05). The A2057G, C2452A, and T2611C gene mutations of 23S rRNA were detected in eight clinical isolates from the azithromycin treatment failure group, while the T2611C gene mutation was detected in one clinical strain from the treatment success group. Conclusions: The detection of resistance genes could better explain the high treatment failure rate than the MIC results in patients with urogenital C. trachomatis infections, highlighting the need for genetic antimicrobial resistance testing in infected patients.